The New Criminal Code And Personal Data Protection In The Digital Era A Critical Analysis Of The Concept Of The Application Of The New Criminal Code - Nugraha, Roby Satya; Hosnah, Asmak Ul; DP, Sapto Handoyo.; Antoni, Herli; Prihatini, Lilik; Saleh, Weldy Jevis; Parreño, Jasmin L. (PALAR (Pakuan Law review), 2025)
AbstractThe purpose of this study is to explain and describe that storing personal data in digital form is considered practical and makes everyone's activities easier, but it has a negative impact in the form of increased crime that follows technological developments, protecting electronic information such as personal data is an important action to protect personal data that is very vulnerable to criminal acts. This journal examines the concept of implementing the 2023 Criminal Code in protecting personal data in the digital era. This study uses a normative legal method with an analysis of statutory regulations. The results of the study show that protecting personal data is the responsibility of the government so that the 2023 Criminal Code has regulated the protection of personal data stored in digital form in criminal acts against informatics and electronics, the implementation of the 2023 Criminal Code will be the basis for regulations that strengthen positive law in protecting personal data that is electronic and stored digitally, law enforcement and written regulations can minimize criminal acts against personal data. In addition to the rules written in the 2023 Criminal Code, real actions are also needed to implement these rules, so that all parties providing justice need to pay attention to the law and provide justice, the public is also expected to be careful in using personal data so that it is not misused by irresponsible parties. Key Words: Criminal Code 2023, Protection of personal data.